The Effect of Organizational Cynicism and Injustice on Counter Productive Behaviors of Staff Considering Demographic Factors - Rahim Rouzbahani (Journal of Global Pharma Technology, 2017)
In recent years, scientists have sought to show a decreasing trend in civil and citizenship behaviors; whereas, unfair and counterproductive interactions and behaviors are increasing. Counterproductive behaviors of a collection include a various range of behaviors such as rudeness, being carefree, robbery and aggressive behaviors towards colleagues and other clients. Meanwhile, counterproductive behaviors are increasingly rising in staff's organizational life. The present research aims to study the effect of organizational cynicism and injustice on counterproductive behaviors of staff in a public hospital considering demographic factors. This is an applied research in terms of objective and a descriptive-survey in terms of nature. Lisrel software and path analysis model were used to test the research hypotheses and to obtain results. According to the hypotheses testing results, the increase of employees' organizational cynicism increases their counterproductive behaviors in a public hospital; the increase of organizational injustice increases employee's counterproductive behaviors; as well as, the increase of organizational injustice increases staff's organizational cynicism in a public hospital.Keywords: Organizational cynicism, Organizational injustice, Counterproductive behaviors, Hospital.